Recent progress in thermosensitive hydrogels and their applications in drug delivery area - Khan, Bangul; Arbab, Areesha; Khan, Samiullah; Fatima, Hajira; Bibi, Isha; Chowdhry, Narinder P.; Ansari, Abdul Q.; Ursani, Ahsan A.; Kumar, Sanjay; Hussain, Jawad; Abdullah, Saad (MedComm - Biomaterials and applications, 2023)
The scientific community has widely recognized thermosensitive hydrogels as highly biocompatible material with immense potential in drug delivery systems. When the temperature of these hydrogels approaches that of human body, a phase change occurs, enhancing their usefulness in a range of medical scenarios. This review article highlighted the background of thermosensitive hydrogels, their properties, and their applications in transdermal, oral, ophthalmic, intravaginal, nasal, rectal, cancer therapy, and cell‐loaded drug delivery systems. The literature suggests numerous advantages of these hydrogels over conventional drug delivery systems and find applications in various fields, such as therapeutic systems, filling processes, and sustained drug delivery systems. One of their key benefits is the ability to eliminate invasive procedures like surgery, providing a noninvasive alternative for drug administration. Moreover, they streamline the formulation process for both hydrophilic and hydrophobic drug delivery systems, simplifying the development of effective treatments. The thermosensitive hydrogels have been found to be green materials with negligible side effects and desirable drug delivery properties. The thermosensitive hydrogel's sustained‐release characteristics, immunogenicity, and biodegradability have also gained increased interest. Some of the disadvantages of thermosensitive hydrogels include delayed temperature response, weak mechanical characteristics, and poor biocompatibility, which limits their potential use in drug delivery applications.